Unspeakable Histories : Film and the Experience of Catastrophe. - Guynn, William (Columbia University Press, 2016)
In Unspeakable Histories, William Guynn focuses on the sensation of encountering past events through film. Film is capable, he argues, of triggering moments of heightened awareness in which the barrier between the past and the present can fall and the reality of the past we thought lost can be momentarily rediscovered in its material being. In his readings of seven exceptional works depicting twentieth century atrocities, Guynn explores the emotional resonance that still adheres to traumatic historical events. Guynn considers dimensions of experience that historiography leaves untouched. Yaël.
Keywords: Historical films -- History and criticism.; Psychic trauma in motion pictures.; Catastrophical, The, in motion pictures.; Electronic books.; Films historiques -- Histoire et critique.; Traumatisme psychique au cinéma.; Catastrophe (Philosophie) au cinéma.; Livres numériques.; e-books.; PERFORMING ARTS -- Reference.; Catastrophical, The, in motion pictures; Historical films; Psychic trauma in motion pictures; Criticism, interpretation, etc.